DIGITAL TRANSFORMATION RESISTANCE AMONG ENGINEERING EMPLOYEES IN HIGH-RISE PROPERTY MANAGEMENT: THE ROLE OF UTAUT AND GENERATIONAL HETEROGENEITY - Gusti Febriyanto; Cosmas G. Haryono; Teofilus Teofilus (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study examines the effects of performance expectancy, effort expectancy, social influence, and facilitating conditions on digital transformation resistance among engineering employees in high-rise property management, while also assessing cross-generational heterogeneity. Using an explanatory quantitative design, data were collected through a survey of 150 respondents working in the Greater Jakarta area. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), followed by Measurement Invariance of Composite Models (MICOM) and Multi-Group Analysis (MGA). The pooled-sample results indicate that performance expectancy and effort expectancy have significant negative effects on digital transformation resistance, whereas social influence does not show a significant effect. Facilitating conditions exhibit a significant positive relationship and are therefore treated as an unexpected finding that requires theoretical caution. The study also finds that most respondents still operate within a hybrid digital-manual system, suggesting that resistance in this context is better understood as a burden of transition rather than as pure anti-technology rejection. Partial measurement invariance is supported only for the comparison between Generation X and Generation Z. Within this boundary, performance expectancy appears more salient for Generation X, whereas effort expectancy appears more salient for Generation Z. Findings involving Generation Y are treated as exploratory and are not used as a basis for strong generalization.